The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2147/rru.s255743
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Systematic Review on Rho-Kinase as a Potential Therapeutic Target for the Treatment of Erectile Dysfunction</p>

Abstract: Background: Erectile dysfunction (ED) is a common clinical condition with limited treatment options. The main aim of the present systematic review was to synthesize information on Rho-kinase as a novel therapeutic approach for the treatment of ED. Methods: We performed a systematic literature study in PubMed, Google Scholar and Scopus. Included studies were original articles studied the role of Rho-kinase in the pathogenesis and/or new treatment approach for ED in animal models and clinical studies, published … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…To this regard, inhibition of RhoA-ROCK signalling seems to potentiate smooth muscle relaxation in an NO-independent manner and could be considered a new therapeutic target for the treatment of ED. [181][182][183] Considering angiotensin-II (Ang II), which is the primary effector of the RAS, studies have demonstrated the presence and activity in the penis. In fact, elevated Ang II levels contribute to the development of ED both in humans and animal models 184 and might be considered as a promising therapeutic target for the treatment of ED.…”
Section: Other Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…To this regard, inhibition of RhoA-ROCK signalling seems to potentiate smooth muscle relaxation in an NO-independent manner and could be considered a new therapeutic target for the treatment of ED. [181][182][183] Considering angiotensin-II (Ang II), which is the primary effector of the RAS, studies have demonstrated the presence and activity in the penis. In fact, elevated Ang II levels contribute to the development of ED both in humans and animal models 184 and might be considered as a promising therapeutic target for the treatment of ED.…”
Section: Other Factorsmentioning
confidence: 99%
“…RhoA/ROCK signalling play a role in the maintaining of the flaccid penile state and its activity in the penis is a pathogenic factor contributing to ED development. To this regard, inhibition of RhoA‐ROCK signalling seems to potentiate smooth muscle relaxation in an NO‐independent manner and could be considered a new therapeutic target for the treatment of ED 181‐183 …”
Section: The ‘Complicated Role’ Of Complications and Cofactors In The...mentioning
confidence: 99%
See 1 more Smart Citation
“…ROCK has two isoforms, ROCK 1 and ROCK 2, which are involved in physiological and pathological signaling pathways (Sopko et al, 2014). ROCK is a primary downstream factor activated through RhoA (Roser et al, 2017;Zewdie et al, 2020). In addition to its regulation of cytoskeletal dynamics, they induced contractile responses in vascular smooth muscle cells (Hirooka and Shimokawa, 2005;Schofield et al, 2012;Loirand, 2015;Zewdie et al, 2020).…”
Section: Analyses On the Relaxation/contraction Responsesmentioning
confidence: 99%
“…ROCK is a primary downstream factor activated through RhoA (Roser et al, 2017;Zewdie et al, 2020). In addition to its regulation of cytoskeletal dynamics, they induced contractile responses in vascular smooth muscle cells (Hirooka and Shimokawa, 2005;Schofield et al, 2012;Loirand, 2015;Zewdie et al, 2020). The RhoA-ROCK activity inhibits eNOS and regulates the contractile state of the sinusoids (Chitaley et al, 2001;Chitaley et al, 2003;Sugimoto et al, 2007;Sopko et al, 2014).…”
Section: Analyses On the Relaxation/contraction Responsesmentioning
confidence: 99%